Activation of specific neuronal networks leads to different seizure onset types. Issue 3 (13th February 2016) - Shiri, Zahra; Manseau, Frédéric; Lévesque, Maxime; Williams, Sylvain; Avoli, Massimo
Abstract : Objective: Ictal events occurring in temporal lobe epilepsy patients and in experimental models mimicking this neurological disorder can be classified, based on their onset pattern, into low‐voltage, fast versus hypersynchronous onset seizures. It has been suggested that the low‐voltage, fast onset pattern is mainly contributed by interneuronal (γ‐aminobutyric acidergic) signaling, whereas the hypersynchronous onset involves the activation of principal (glutamatergic) cells. Methods: Here, we tested this hypothesis using the optogenetic control of parvalbumin‐positive or somatostatin‐positive interneurons and of calmodulin‐dependent, protein kinase–positive, principal cells in the mouse entorhinal cortex in the in vitro 4‐aminopyridine model of epileptiform synchronization. Results: We found that during 4‐aminopyridine application, both spontaneous seizure‐like events and those induced by optogenetic activation of interneurons displayed low‐voltage, fast onset patterns that were associated with a higher occurrence of ripples than of fast ripples. In contrast, seizures induced by the optogenetic activation of principal cells had a hypersynchronous onset pattern with fast ripple rates that were higher than those of ripples. Interpretation: Our results firmly establish that under a similar experimental condition (ie, bath application of 4‐aminopyridine), the initiation of low‐voltage, fast and of hypersynchronous onset seizures in the entorhinal cortex depends on the preponderant involvement of interneuronal and principal cell networks, respectively. Ann Neurol 2016 ANN NEUROL 2016;79:354–365